Analysis of Principal Performance in Managing Human Resources at SD Negeri 17 Palu - Nurhabiba; Bakri Hasanuddin; Yoberth kornelius; Riswandi palawa (Journal of Humanities, Community Service, and Empowerment, 2024)
This study aims to analyze the performance of the principal in managing human resources at SD Negeri 17 Palu. The primary focus of this study is on key aspects, including the recruitment and selection of educators, performance evaluation, interpersonal relationships among staff, conflict management, and parent involvement. The approach used in this study is qualitative, employing a case study method that collects data through in-depth interviews with teachers, the principal, and field observations. The results of the study indicate that the principal has not been fully effective in managing human resources, particularly in aspects such as recruitment and performance evaluation, which are less transparent and less than optimal in terms of conflict management. The principal's performance in managing human resources affects the working conditions in the school as well as the quality of education provided. Nepotism practices in teacher recruitment and selection, as well as a lack of transparency in performance evaluation, have eroded staff trust in the principal's leadership. Additionally, poor interpersonal relationships between the principal and staff have exacerbated the working environment. However, parental involvement in various school activities is considered positive. This study recommends that principals enhance their recruitment processes, performance evaluations, and conflict management strategies to create a fairer and more productive environment.